2000
DOI: 10.1111/j.1525-1373.2000.22524.x
|View full text |Cite
|
Sign up to set email alerts
|

One‐Year Effects of Increasingly Fat‐Restricted, Carbohydrate‐Enriched Diets on Lipoprotein Levels in Free‐Living Subjects

Abstract: Abstract. Restriction of all dietary fat is a popular strategy for restricting saturated fat intake to lower LDL cholesterol. Some authorities advise the restriction of fat intake to the extreme of less than 10% of daily energy on the assumption that more fat restriction is better. The two studies described herein address questions relating to whether increasing fat restriction produces proportionally increasing benefit on cardiovascular risk factors in hyperlipidemic subjects.The first study is the Dietary Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Palmitic, oleic, and linoleic acids constitute up to 70% of circulating FFA in humans, with each typically being present in concentrations between 10–50 μM 21, 22. Although the current cell culture studies relied upon concentrations of palmitic acid (100 μM) higher than those usually found in humans, lower concentrations of palmitic/BSA (50 μM) also increase endothelial levels of IL-6.…”
Section: Discussionmentioning
confidence: 93%
“…Palmitic, oleic, and linoleic acids constitute up to 70% of circulating FFA in humans, with each typically being present in concentrations between 10–50 μM 21, 22. Although the current cell culture studies relied upon concentrations of palmitic acid (100 μM) higher than those usually found in humans, lower concentrations of palmitic/BSA (50 μM) also increase endothelial levels of IL-6.…”
Section: Discussionmentioning
confidence: 93%
“…21 Interestingly, membrane levels of 16:1n-7 in the present study was also related to body weight, possibly reflecting the effects of low-fat high-carbohydrate diets on de novo synthesis and hypertriglyceridemia. 10, 11 The fatty acid 16:1n-7 was highly correlated with its precursor 16:0 and the association of 16:0 with SCA risk appeared more robust than that of 16:1n-7. However, this difference in level of association cannot be concluded from the study data.…”
Section: Discussionmentioning
confidence: 95%
“…29 The occurrence of fatty acid synthesis from dietary carbohydrates in the absence of excess caloric intake is supported by dietary trials. 8, 9 10-12 Further studies are needed to investigate dietary and genetic factors that promote fatty acid synthesis. The associations of end products of fatty acid synthesis with SCA risk raise the possibility that dietary carbohydrates in the setting of low fat intake might also be associated with SCA risk.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that metabolic pathways are the primary determinant of circulating levels. One key driver of higher circulating 16:0 appears to be de novo lipogenesis, an endogenous enzymatic pathway by which dietary carbohydrates are converted into circulating fatty acids in the presence of low‐fat and high‐carbohydrate diets . Alcohol intake may also drive the endogenous synthesis of 16:0 …”
Section: Discussionmentioning
confidence: 99%
“…The SFAs palmitic acid (16:0) and stearic acid (18:0) are found in animal products, such as meat and hard cheeses, and in tropical oils, whereas arachidic acid (20:0), behenic acid (22:0), and lignoceric acid (24:0) are found in peanuts and canola oil. SFA 16:0 is also the primary end product of fatty acid synthesis, and circulating levels of 16:0 are influenced by carbohydrate and alcohol intake …”
Section: Introductionmentioning
confidence: 99%